Effects of glass fibers reinforced and non-reinforced composite resin on fracture behavior of severely destructed primary incisors and restored with post and core system - Rizk El Agamy (Elsevier, 2024)
Objective: To evaluate fracture resistance and failure type of coronally rehabilitated primary incisors with EverX Flow or Grandio Core post and core with or without fiber post. Materials and Methods: Forty-eight extracted maxillary primary incisors were root canal treated and obturated with Metapex. The coronal 4-mm of Metapex was removed to create 3-mm intracanal post space. Next, coronal enamel and radicular dentin surfaces were acid-etched, and a bonding agent was applied and light-cured. Based on intracanal post and 2-mm height core buildup materials, specimens were divided equally (n = 12) into 4 groups as follow; Group I (EverX Flow), Group II (Grandio Core), Group III (Fiber post, and EverX Flow), and Group IV(Fiber post and Grandio Core). The coronal restorations were finalized to 4-mm height using G-aenial Anterior composite and specimens were tested for fracture resistance. Force required to induce fracture was recorded and failure type was examined. Results: Fracture resistance of Fiber post and EverX Flow group was statistically significant high than other tested groups. However, fracture resistance of EverX Flow group showed non-statistically significant difference from that of Fiber post and Grandio Core group. Regarding failure type, no specimen presented root fracture, and all failures were favorable and repairable. Conclusion: EverX flow post and core with or without fiber post enhanced fracture resistance of restored primary incisors compared to Grandio Core alone. Clinical relevance: EverX flow post and core system with or without fiber post could be a promising restorative option for severely destructed primary incisors.